Evaluation of the potential malting, brewing and antiyeast characteristics of selected Zambian sorghum cultivars - Valashiya, Rorisang Cynthia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScFoodSc)--Stellenbosch University, 2014.